2013
DOI: 10.1111/imm.12169
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐specific B lymphocytes acquire proteoglycan aggrecan from cartilage extracellular matrix resulting in antigen presentation and CD4+T‐cell activation

Abstract: SummaryThe majority of studies examining antigen-presenting cell (APC) function have focused on the capture and presentation of antigens released from pathogens or damaged cells. However, antigen-specific B cells are also capable of efficiently extracting antigens that are either tethered to, or integrally part of the plasma membrane of various target cells. In this study we show that B cells are also highly efficient at extracting integral components of the extracellular matrix (ECM) for subsequent presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
(104 reference statements)
1
21
0
Order By: Relevance
“…We observed degradation of synaptic antigen when it was tethered strongly to a noninternalizable surface, in agreement with previous studies using antigen covalently coupled to noninternalizable latex beads (Yuseff et al, 2011;Reversat et al, 2015). It is possible that enzymatic degradation plays a role in antigen acquisition from stiff physiological substrates such as bone (Li et al, 2010), cartilage (Ciechomska et al, 2014), or bacterial biofilms (Gil et al, 2014). The fragments of antigen liberated in this process are endocytosed by unknown pathways, but do lead to peptide loading onto MHC II (Yuseff et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…We observed degradation of synaptic antigen when it was tethered strongly to a noninternalizable surface, in agreement with previous studies using antigen covalently coupled to noninternalizable latex beads (Yuseff et al, 2011;Reversat et al, 2015). It is possible that enzymatic degradation plays a role in antigen acquisition from stiff physiological substrates such as bone (Li et al, 2010), cartilage (Ciechomska et al, 2014), or bacterial biofilms (Gil et al, 2014). The fragments of antigen liberated in this process are endocytosed by unknown pathways, but do lead to peptide loading onto MHC II (Yuseff et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…More importantly, it is known that substrate stiffness can regulate the proliferation and differentiation of mesenchymal stem cells (MSCs) and ES cells [19,20]. For example, softer substrates (0.1-1 kPa) tend to cause MSCs to differentiate into neuronal cells, whereas stiffer substrates (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) give rise to myocyte-like cells and the stiffest substrate (25-40 kPa) results in osteoblast-like cells [21]. These studies suggest that the downstream proliferation and differentiation of B cells following the initiation of their activation might also be subjected to the regulation of substrate stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the stiffness of extracellular matrix (ECM) in the tissue spans a considerable range from 12 Pa to 20 kPa [12,[14][15][16]. A very recent study showed that aggrecan, an integral component of cartilage ECM, can be efficiently acquired by autoreactive B cells in a BCR and contact-dependent manner [17].Given these facts, there are, however, limited studies investigating how the stiffness features of the substrates presenting the antigens regulate the response of B cell upon BCR engagement. A recent study by Tolar and his colleagues showed that B cells use mechanical energy to test the strength of antigen binding and by doing so to discriminate antigen affinity [18].…”
mentioning
confidence: 99%
“…This is because T cells are interacting with B cells that can function as APC during chronic inflammatory diseases (5153). Cognate T and B cells interact and provide reciprocal help required for activation and differentiation of both cell types, which results in alterations in both T- and B-cell populations (9, 52).…”
Section: Discussionmentioning
confidence: 99%